Metonymy as a cognitive-inferential mechanism in communication; La metonimia como mecanismo cognitivo-inferencial en la comunicación - Cardenas-Mancilla, M (Universidad de Santiago de Chile, 2025)
This article examines metonymy as a cognitive-inferential phenomenon from two main theoretical approaches: Cognitive Linguistics (CL) and Relevance Theory (RT). While CL emphasizes its role in conceptualization and categorization through contiguity-based relationships within the same conceptual domain, RT highlights its pragmatic function by guiding interpretation through contextually driven inferences. Metonymy is analyzed both as a referential mechanism that allows mental access to related entities and as an inferential trigger that functions as a procedural instructor for the hearer. Through a comparative discussion, it is argued that both perspectives are complementary and that an integrative view enables an understanding of metonymy as a multidimensional process operating on conceptual, pragmatic, and communicative levels. © 2025, Universidad de Santiago de Chile. All rights reserved.